SURVEY OF SATISFACTION OF PAUD TEACHERS ON MEDIA MAKING EARTHQUAKE MITIGATION LEARNING - Nababan, Marina; Agustina, Winarti; Simamora, May Rauli (JURNAL TALITAKUM: JURNAL PENDIDIKAN KRISTEN ANAK USIA DINI, 2023)
Earthquake mitigation learning media is very effectively used in learning in PAUD institutions. It is easier for young children to gain understanding and experience when learning at school is displayed in the form of learning media. This learning media was created with the aim of educating young children in earthquake preparedness. The results of the survey research show that PAUD teachers are satisfied and happy with the existence of earthquake mitigation learning media. This learning media can be implemented well in learning activities for early childhood in PAUD institutions. Keywords: learning media, mitigation, earthquakes